POTENSI âSANGGA BUWANAâ DENGAN SUBSTITUSI TEPUNG SUKUN SEBAGAI MAKANAN SIAP SAJI YANG SEHAT - Arnold, Marcellus; Lawandra, Rio; Rajagukguk, Yolanda Victoria; Oktaviani, Tri; Emely, Emely (Nutri-Sains: Jurnal Gizi, Pangan dan Aplikasinya, 2017)
During the reign of Sri Sultan Hamengkubuwono VII at Yogyakarta Palace, Sangga Buwana is a traditional food which arose up as a result of acculturation between local culture with European and Asian culture. The food symbolizes a confession of human towards the existence of God. When comparing to burger in terms of ingredients and the manner of serving, both of them are quite similar. The purpose of this research is to study the potency of Sangga Buwana as a healthier fast food than burger. In addition, the investigation of the potency of local food utilization such as breadfruit (Artocorpus altilis) flour as wheat flour substitution in preparation of choux dough is also conducted. The study is conducted by literature research and interviews. The results showed that the substitution of wheat flour to breadfruit flour is potential to make Sangga Buwana as a healthier fast food because it has richer fiber, higher mineral, and lower fat content than wheat flour. Breadfruit flour can partially substitute the usage of wheat flour in the preparation of choux dough.